THE INTERACTION BETWEEN TAX POLICY INNOVATION AND CORPORATE TAX AVOIDANCE STRATEGIES IN THE DIGITAL ECONOMY - Loso Judijanto; Devia Septyani; Amirah Andika Rifdayanti (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2026)
The development of the digital economy has fundamentally changed the way companies create value, conduct business activities, and manage tax obligations across jurisdictions. This transformation has prompted governments in various countries to develop innovative tax policies aimed at maintaining the tax base, improving fiscal fairness, and curbing corporate tax avoidance practices. On the other hand, multinational corporations in the digital era also continue to adapt increasingly complex tax avoidance strategies by exploiting digital economic characteristics such as intangible assets, profit mobility, and platform-based business structures. This study aims to analyze the interaction between tax policy innovation and corporate tax avoidance strategies in the context of the digital economy through a literature review method. The review was conducted on scientific articles, international organization reports, and relevant global tax regulations, including digital tax policies, Base Erosion and Profit Shifting (BEPS), and the global minimum tax. The results of the study indicate that tax policy innovation is often reactive to evolving tax avoidance practices, while companies tend to respond to these policies with more sophisticated strategic adjustments. This dynamic interaction creates a cycle of mutually influencing policies and strategies, which demands an adaptive, collaborative, and global governance-based regulatory approach. This research is expected to provide a conceptual contribution to understanding the relationship between tax policy and corporate behavior in the digital era and serve as a reference for formulating more effective and sustainable tax policies.